Prairie Town: Rural Life and Literacies - Jacqueline Edmonson (Journal of Research in Rural Education, 2001)
Prairie Town, MN (population 5,067), a community on the rural midwestern prairie, isfacing changes as the longstanding agricultural crisis and neoliberalism impact daily life and education in this town. This study, analyzed through a sociopolitical literacy lens, reports the conditions oflife and work in this community as residents work to redefine and reestablish what it means to be rural.